Localization System for Wireless Sensor Networks - Singha, Anjani Kumar; Singla, Anshu; Gupta, Sudhir (IJRDO -Journal of Computer Science Engineering, 2016)
Sensors are frequently being used for monitoring different phenomena of environment, Military, Health, Industry, Automobiles etc., and the information derived from sensed data are being used for making important decisions which directly affects humans and at times human life. This sensed data can only be of use if we know the exact position of the sensor node. This is not always easy as in many real life scenario, the deployment is random and in hostile conditions. Further, replacing a dead or damaged node is not an option in many circumstances. Many different approaches have been proposed by research community for localization information of a node deployed in a target area. In this work, an attempt has been made to review most promising localization methods proposed so far in comparative manner.